Pengaruh Pengembangan Karir Bank Aceh Syariah - Josi Farmiati; Ismail Ismail (Jurnal EMT KITA, 2021)
The purpose of this study was to determine whether career development has an effect on employee performance, and to determine the magnitude of the effect of career development on employee performance. The location of this research was conducted at PT. Aceh Sharia Bank. The object of this research is all employees at PT. Bank Aceh Syariah, with a total research sample of 217 people who have received a career development training program. Data was collected by distributing questionnaires (list of questions), which had been prepared to the respondents. The collected data was then analyzed using multiple linear regression formulations with the help of SPSS software. The results of this study indicate that career development has a positive and significant effect on the performance of employees of PT. Bank Aceh Syariah.